HIF Prolyl Hydroxylase Inhibitors for COVID-19 Treatment: Pros and Cons - Poloznikov, Andrey A.; Nersisyan, Stepan A.; Hushpulian, Dmitry M.; Kazakov, Eliot H.; Tonevitsky, Alexander G.; Kazakov, Sergey V.; Vechorko, Valery I.; Nikulin, Sergey V.; Makarova, Julia A.; Gazaryan, Irina G. (Frontiers in Pharmacology, 2021)
The review analyzes potential advantages and problems associated with using HIF prolyl hydroxylase inhibitors as a treatment for COVID-19. HIF prolyl hydroxylase inhibitors are known to boost endogenous erythropoietin (Epo) and activate erythropoiesis by stabilizing and activating the hypoxia inducible factor (HIF). There is little doubt that Epo treatment has anti-inflammatory and healing properties, and thus will be beneficial for moderate to severe cases of COVID-19. However, in addition to stimulating Epo production, HIF PHD inhibition may have a significantly broader effect. The analysis of HIF target genes reveals that some HIF-targets, such as furin for example, could play a negative role with respect to viral entry. On the other hand, HIF prolyl hydroxylase inhibitors counteract ferroptosis, the process recently implicated into vessel damage during COVID-19 later stages. Therefore, HIF prolyl hydroxylase inhibitors may be a promising treatment of COVID19 complications, but are unlikely to aid in the prevention of the initial stages of infection.